Evaluating teaching practices in graduate programs (2019)
Today, educational evaluation is one of the pillars on which the quality of universities and, therefore, the quality assurance systems in higher education institutions are based. This has allowed, from an institutional evaluation approach, to relate aspects concerning the institutional mission or project, academic resources, curricula, physical and financial resources, as well as teaching-learning processes, in which students and teachers play a leading role. It seems that there is a certain consensus on the part of the scientific community that specialises in this field on the meaning of evaluation as a process that transcends a perspective of measurement or observation to become a tool that seeks to contribute to the improvement of the quality of teaching processes and integrates professor development as a transversal element